The art of say more about that : ...and other ways to speak up, push back, and advocate for yourself and others - Cabral, Amber (Wiley, 2022)
"The art of pushing back and speaking up is a logical follow-up to Amber Cabral's first book, Allies and Advocates. It offers even more tactical steps to help people address inequitable treatment and gives them the tools to call it out when they see it. Instead of passive-aggressive language, shrinking, or ghosting, this book will give the reader a communications toolkit for self-advocacy and advocating for others. The Art of Pushback will equip the reader with the tools to call out wrongdoing at home, at work, and in public settings. Where Allies and Advocates challenged the reader to "be brave," this book will provide tactics, context, and tools including sample scripts and other communications templates to make the prospect of bravery less daunting."--